Ion Transport through Diffusion Layer Controlled by Charge Mosaic Membrane - Akira Yamauchi (International Journal of Chemical Engineering)
The kinetic transport behaviors in near interface of the membranes were studied using commercial anion and cation exchange membrane and charge mosaic membrane. Current-voltage curve gave the limiting current density that indicates the ceiling of conventional flux. From chronopotentiometry above the limiting current density, the transition time was estimated. The thickness of boundary layer was derived with conjunction with the conventional limiting current density and the transition time from steady state flux. On the other hand, the charge mosaic membrane was introduced in order to examine the ion transport on the membrane surface in detail. The concentration profile was discussed by the kinetic transport number with regard to the water dissociation (splitting) on the membrane surface.